Techno-Economic Analysis of Centralized Protection and Control Systems - Sorvala, Sami (My University, 2025)
This thesis investigates the technical feasibility and economic impact of centralized protection and control (CPC) systems in medium- and high-voltage substations, especially from the point of view of the contractor. One centralized protection and control product can be capable of handling the protection and control tasks of up to 30 traditional protection relays. Centralizing protection and control functions offers several advantages, including cost savings, advanced protection functions and capabilities, and improved fault diagnostics. The study begins with a literature review of the technologies and architectures that enable centralized protection and control schemes, such as IEC 61850 communication standards, process bus applications, redundancy protocols, and the use of intelligent electronic devices. In addition, CPC products currently available on the market are reviewed and compared, providing a foundation for the subsequent analysis. Existing literature about the economic impact of implementing centralized protection and control solutions is rather limited, but the available studies suggest that CPC systems can offer significant cost savings, reduced device counts, and simplified maintenance compared to traditional decentralized architectures. Two case studies of real-life substation projects were carried out to evaluate the practical implications of CPC adoption. The first case study examined a large, complex 110/20 kV substation with demanding protection requirements, while the second focused on a mediumscale substation with simpler architecture. The findings indicate that while CPC systems are technically mature and feasible, their economic attractiveness depends strongly on the scale and configuration of the substation. In large-scale projects, where the protection requirements are demanding, the high costs of CPC units and integration can outweigh potential savings, whereas in smaller and simpler substations, CPC solutions can offer clear capital and operational cost advantages. Beyond cost considerations, CPC offers several long-term operational benefits, including reduced device count, simplified maintenance and testing, and improved scalability for future system upgrades. However, challenges remain in terms of engineering complexity, training requirements in a rapidly evolving field, and integration with established practices. The results of this thesis indicate that CPC solutions are not universally optimal but can provide significant value under the right circumstances.

Tässä diplomityössä tutkitaan keskitettyjen suojaus- ja ohjausjärjestelmien teknistä toteutettavuutta ja taloudellisia vaikutuksia keski- ja suurjännitesähköasemilla, erityisesti urakoitsijan näkökulmasta. Yksi keskitetyn suojauksen tuote voi pystyä hoitamaan jopa 30 perinteisen suojareleen tehtävät. Suojaus- ja ohjaustoimintojen keskittäminen tarjoaa useita etuja, kuten kustannussäästöjä, kehittyneitä suojatoimintoja ja parannettua vikadiagnostiikkaa. Tutkimus alkaa kirjallisuuskatsauksella teknologioista ja arkkitehtuureista, jotka mahdollistavat keskitetyt suojaus- ja ohjausjärjestelmät, kuten IEC 61850 -kommunikaatiostandardi, prosessiväyläsovellukset, redundanssiprotokollat ja automaatiolaitteiden käyttö. Lisäksi työssä tarkastellaan ja vertaillaan markkinoilla tällä hetkellä saatavilla olevia keskitetyn suojauksen ja ohjauksen tuotteita, mikä luo perustan myöhemmälle analyysille. Keskitettyjen suojaus- ja ohjausratkaisujen taloudellisista vaikutuksista on olemassa vain rajoitettu määrä tutkimuksia, mutta saatavilla olevat tutkimukset viittaavat siihen, että keskitetyn ohjauksen ja suojauksen järjestelmät voivat tarjota merkittäviä kustannussäästöjä, vähentää laitemäärää ja yksinkertaistaa huoltoa verrattuna perinteisiin hajautettuihin järjestelmiin. Työssä toteutettiin kaksi tapaustutkimusta oikeista sähköasemaprojekteista. Ensimmäinen tapaus käsitteli suurta ja monimutkaista 110/20 kV sähköasemaa, jossa oli vaativat suojausvaatimukset, kun taas toinen keskittyi keskisuureen sähköasemaan, jonka arkkitehtuuri oli yksinkertaisempi. Tulokset osoittavat, että vaikka keskitetyt järjestelmät ovat teknisesti kypsiä ja toteuttamiskelpoisia, niiden taloudellinen houkuttelevuus riippuu vahvasti sähköaseman koosta ja kokoonpanosta. Suurissa ja vaativissa projekteissa keskitettyjen laitteiden ja integroinnin korkeat kustannukset voivat ylittää mahdolliset säästöt, kun taas pienemmissä ja yksinkertaisemmissa sähköasemissa keskitetyt ratkaisut voivat tarjota selkeitä etuja sekä pääoma- että käyttökustannuksissa. Kustannustekijöiden lisäksi keskitetty suojaus tarjoaa useita pitkän aikavälin käyttökustannusetuja, kuten vähentyneen laitemäärän, yksinkertaistetun huollon ja testauksen sekä parannetun skaalautuvuuden tulevia järjestelmäpäivityksiä varten. Haasteita kuitenkin edelleen esiintyy, erityisesti suunnittelun monimutkaisuuden, nopeasti kehittyvän alan koulutustarpeiden ja olemassa olevien käytäntöjen integroinnin osalta. Työn tulokset osoittavat, että keskitetyt suojaus- ja ohjausratkaisut eivät ole universaalisti optimaalisia, mutta ne voivat tarjota merkittäviä etuja oikeissa olosuhteissa.
Keywords: fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master’s Programme in Smart Energy